Biogenic sediments of peatlands in the Łódź region as material for research on fossil Cla-docera - Rudna, Marta; Forysiak , Jacek (Acta Geographica Lodziensia, 2024)
This paper shows the origin and geomorphological diversity of peatlands in the Łódź region and the variable lith-ology of the sediments filling their depressions. The suitability of biogenic sediments deposited in such forms for paleoeco-logical analyzes was assessed. A review of previous research highlights analyzes of cladoceran fossil remains. The content indicates the scope of such analyzes over the last dozen or so years and their importance for the reconstruction of paleogeographic changes in the Late Vistulian and Holocene. Other important goals of the synthesis are to indicate the importance of high-resolution studies and to assess the validity of their performance.